2012
DOI: 10.1186/1756-0500-5-482
|View full text |Cite
|
Sign up to set email alerts
|

Re-challenge with pemetrexed in advanced mesothelioma: a multi-institutional experience

Abstract: BackgroundAlthough first-line therapy for patients affected by advanced mesothelioma is well established, there is a lack of data regarding the impact of second-line treatment.MethodsWe retrospectively collected data of patients affected by advanced mesothelioma, already treated with first-line therapy based on pemetrexed and platin, with a response (partial response or stable disease) lasting at least 6 months, and re-treated with a pemetrexed-based therapy at progression. The primary objective was to describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 26 publications
3
33
0
Order By: Relevance
“…Patients with a TFS of ≥3 months also exhibited a longer PFS2 compared to those with a TFS of <3 months. Such results are similar to those reported by previous studies on MPM patients (4,6). However, the cut-off value of PFS1 in this study was shorter compared to that in the study of Ceresoli et al (4) (10 vs. 12 months, respectively).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Patients with a TFS of ≥3 months also exhibited a longer PFS2 compared to those with a TFS of <3 months. Such results are similar to those reported by previous studies on MPM patients (4,6). However, the cut-off value of PFS1 in this study was shorter compared to that in the study of Ceresoli et al (4) (10 vs. 12 months, respectively).…”
Section: Discussionsupporting
confidence: 90%
“…It was recently demonstrated that PBC may be used as rechallenge treatment in MPM patients who achieve a PFS ≥12 months with first-line PBC (4)(5)(6). We have also noticed in clinical practice that certain patients with non-squamous NSCLC benefited from rechallenge with PBC as second-or further-line treatment.…”
Section: Introductionmentioning
confidence: 87%
“…Generally, it is suggested that retreatment should be considered in patients achieving an at least 12-month disease control with first-line therapy [16,18]. Our data seem to support this idea, and, according to our experience, we feel that second-and third-line treatments are inappropriate in patients not responding to firstline therapy.…”
Section: Discussionsupporting
confidence: 75%
“…In everyday clinical practice, a second-line CT is offered at progression. Median survival varies between 10.5 and 13.6 months for re-challenge with a pemetrexed-based therapy, and between 6.2 and 20.8 months in patients treated with other CTs [11,16,18].…”
Section: Discussionmentioning
confidence: 99%
“…Bearz et al selected 30 patients from 7 Italian centers in a retrospective study (9). Mesothelioma histology was epithelioid in 28 patients and mixed in 2, 1 patient had an extra pleural localization in the tunica vaginalis.…”
Section: Rechallenge With Pemetrexedmentioning
confidence: 99%